Reforming Civil Service in Sierra Leone through Collective Leadership - World Bank (Washington, DC, 2014)
Improved capacity of the civil service in Sierra Leone is critical to deliver services for citizens. The government is tackling challenges of poor performance through a flagship public sector reform program (improving productivity through management and pay reforms), a part of which involves reform of the civil service. The World Bank is supporting the government on this civil service reform through a lending project on pay and performance. The project targets changes in three areas: (1) competitiveness in the pay of civil servants; (2) performance management and accountability of civil servants; and (3) recruiting and staffing to fill key positions. The World Bank leadership practice is supporting a collaborative leadership process to advance the pay and performance project results. They provided rapid results approach (RRA) coaching to approximately five inter-agency implementation teams to achieve the indicators set by the project, and facilitated discussions with the teams and the leadership team for the civil service reform agenda, in order to review progress and conduct problem-solving that will address implementation challenges.